Genomic era diagnosis and management of hereditary and sporadic colon cancer - Esplin, Edward David (World J Clin Oncol, 2014)
The morbidity and mortality attributable to heritable and sporadic carcinomas of the colon are substantial and affect children and adults alike. Despite current colonoscopy screening recommendations colorectal adenocarcinoma (CRC) still accounts for almost 140000 cancer cases yearly. Familial adenomatous polyposis (FAP) is a colon cancer predisposition due to alterations in the adenomatous polyposis coli gene, which is mutated in most CRC. Since the beginning of the genomic era next-generation sequencing analyses of CRC continue to improve our understanding of the genetics of tumorigenesis and promise to expand our ability to identify and treat this disease. Advances in genome sequence analysis have facilitated the molecular diagnosis of individuals with FAP, which enables initiation of appropriate monitoring and timely intervention. Genome sequencing also has potential clinical impact for individuals with sporadic forms of CRC, providing means for molecular diagnosis of CRC tumor type, data guiding selection of tumor targeted therapies, and pharmacogenomic profiles specifying patient specific drug tolerances. There is even a potential role for genomic sequencing in surveillance for recurrence, and early detection, of CRC. We review strategies for diagnostic assessment and management of FAP and sporadic CRC in the current genomic era, with emphasis on the current, and potential for future, impact of genome sequencing on the clinical care of these conditions.